Demystifying a shining example: German public finances under the debt brake - Kai Eicker-Wolf; Achim Truger (International Labour Organization (ILO), 2014)
German fiscal policy is nowadays often presented as a shining example due to successful budget consolidation after the Great Recession. However, the idea that the German success is the result of a well-thought-out economic strategy that could therefore serve as a role model for other countries does not stand up to closer scrutiny. First of all, Germany's fiscal policy escaped from an absolutely bleak outlook just three years ago only due to extraordinarily good luck. A completely unexpected soaring economic upturn in 2010 and 2011 led to the substantial easing of the burden on Germany's public budgets. Second, if the economy nosedived, public budgets would again be faced with severe cyclical constraints. Third, below the surface of the balanced government budget severe structural deficiencies of German tax and fiscal policies are hidden: excessive tax cuts in the past have led to continuing structural shortfalls in the budget that in turn caused a serious neglect of undisputedly necessary essential investments in the future of education, research and infrastructure. As long as the debt brake is in place, in order to overcome these deficiencies socially just tax increases should be used to finance the spending needs. It turns out, that to date a real policy shift in this direction is still lacking.
Additional information: This paper is a substantially revised and updated translation of Eicker-Wolf, K./Truger, A. (2013): Staatliche Handlungsfähigkeit und Zukunftsinvestitionen unter der Schuldenbremse. Die deutsche Steuer- und Finanzpolitik am Scheideweg, in: Eicker-Wolf, K./Quaißer, G./Thöne, U. (eds.): Bildungschancen und Verteilungsgerechtigkeit. Grundlagen für eine sachgerechte Bildungs- und Finanzpolitik, Marburg: Metropolis: 101-136. Translation by Ian Graham.
Keywords: 330; taxation; fiscal policy; public expenditure; investment; Germany